2017
DOI: 10.15628/holos.2017.6445
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Uso De Biomassa Bacteriana Imobilizada Na Biossorção De Terras-Raras Leves E Médias

Abstract: A busca por fontes alternativas de recuperação e separação dos elementos puros de terras--raras (TRs) é vista como uma ação prioritária e estratégica por diversos países demandantes desses elementos. Em alternativa aos processos clássicos de extração de TRs, o processo de biossorção vem sendo avaliado, em uma combinação da biotecnologia e metalurgia extrativa. Sendo assim, o presente trabalho buscou avaliar a capacidade da biomassa imobilizada da bactéria Bacillussubtilis na biossorção de lantânio (TR leve) e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Predicting the possibility of increasing the concentration of lanthanides in effluents have been carried out using microbial cells immobilized on Ca 2+ alginate for rare earth biosorption processes. Ca 2+ alginate immobilized biomass of Bacillus subtilis was applied for La and Sm biosorption studies with high percentual of rare earth removal, 94.4 and 94.9 %, respectively (Coimbra et al 2017). The kinetic study of La biosorption, in concentrations ranging 10-100 mg/L, showed that Ca 2+ alginate microalgal immobilized biosorbents formed by Ankistrodesmus sp.…”
Section: Biosorption For Metal Bioremediation In Contaminated Mining ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting the possibility of increasing the concentration of lanthanides in effluents have been carried out using microbial cells immobilized on Ca 2+ alginate for rare earth biosorption processes. Ca 2+ alginate immobilized biomass of Bacillus subtilis was applied for La and Sm biosorption studies with high percentual of rare earth removal, 94.4 and 94.9 %, respectively (Coimbra et al 2017). The kinetic study of La biosorption, in concentrations ranging 10-100 mg/L, showed that Ca 2+ alginate microalgal immobilized biosorbents formed by Ankistrodesmus sp.…”
Section: Biosorption For Metal Bioremediation In Contaminated Mining ...mentioning
confidence: 99%
“…For example, the use of immobilized cells in bioleaching (Martínez and Parada 2013), heavy metals Khare 2012, Mishra 2013), mercury and rare-earth elements biosorption (Coimbra et al 2017, Corrêa et al 2017, Coimbra et al 2019, acid mine drainage (Long et al 2004), bioremediation (Zommere and Nikolajeva 2017), and H 2 S removal (Chung et al 2010) have all been examined. However, most of these investigations were perfomed at laboratorial level, and applications of immobilized cells in mining activities in the open environment and industrial scale have yet to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…4.1 Interações entre micro-organismos e minerais Na última década, vários estudos têm sido publicados abordando as interações entre micro-organismos e minerais portadores de TRs, incluindo a solubilização de TRs a partir de matrizes sólidas por meio de reações com metabólitos microbianos (Zhang et al, 2018) e a imobilização de TRs de matrizes líquidas, principalmente por sorção por biomassa (Coimbra, Nascimento & Giese, 2017;Heidelmann et al, 2017;Coimbra et al, 2019;Giese, Barbosa-Dekker & Dekker, 2019;Giese & Jordão, 2019).…”
Section: Biolixiviação De Minérios Portadores De Terras Rarasunclassified
“…According to Kim & Osseo-Asare [6], monazite undergoes physical processing first, followed by chemical processing, which can occur through acid treatment using sulfuric acid. The sulfate (SO4 2-) ion of sulfuric acid can act as a ligand which reacts with REE as follows [7]: 2REEPO4(s) + 3H2SO4 = (REE)2(SO4)3(s) + 6H + + 2PO4 -3 In the last decade, several studies have been published addressing the interactions between microorganisms and minerals carrying REE, including the solubilization of REE from definite matrices through reactions with microbial metabolites [8] and immobilization of REE of liquid matrices, mainly by sorption by biomass [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%